2019
DOI: 10.1101/836262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CenH3-independent kinetochore assembly in Lepidoptera requires CENP-T

Abstract: Accurate chromosome segregation requires assembly of the multiprotein kinetochore complex at centromeres. In most eukaryotes, kinetochore assembly is primed by the histone H3 variant CenH3, which physically interacts with components of the inner kinetochore constitutive-centromereassociated-network (CCAN). Unexpected to its critical function, previous work identified that select eukaryotic lineages, including several insects, have lost CenH3, while having retained homologs of the CCAN. These findings imply alt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 72 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Surprisingly, previous work found that a subset of insect species has lost CENP-A, even though other canonical centromere proteins are retained [7]. Now, the work from Cortes-Silva et al [6] provides insights into the molecular composition and organization of Lepidopteran kinetochores, in which both the loss of CENP-A and a gain of holocentromeres have occurred.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, previous work found that a subset of insect species has lost CENP-A, even though other canonical centromere proteins are retained [7]. Now, the work from Cortes-Silva et al [6] provides insights into the molecular composition and organization of Lepidopteran kinetochores, in which both the loss of CENP-A and a gain of holocentromeres have occurred.…”
mentioning
confidence: 99%
“…Finally, the plasticity of the kinetochore is also highlighted by changes in the conservation of kinetochore proteins through both substantial changes to their protein sequences and even the loss of selected kinetochore proteins across evolution [4,5]. Now, new work by Cortes-Silva et al [6] in this issue of Current Biology reveals molecular rewiring of kinetochores in holocentric insect species in the order Lepidoptera (which includes butterflies and moths), highlighting changes in kinetochore organization whereby core kinetochore proteins are lost and centromere structure is altered.…”
mentioning
confidence: 99%
See 1 more Smart Citation